High Voltage Operation of Ni‐Rich NMC Cathodes Enabled by Stable Electrode/Electrolyte Interphases - Zhao, Wengao; Zheng, Jianming; Zou, Lianfeng; Jia, Haiping; Liu, Bin; Wang, Hui; Engelhard, Mark H.; Wang, Chongmin; Xu, Wu; Yang, Yong; Zhang, Ji‐Guang (Advanced energy materials, 2018)
The lithium (Li) metal battery (LMB) is one of the most promising candidates for next‐generation energy storage systems. However, it is still a significant challenge to operate LMBs with high voltage cathodes under high rate conditions. In this work, an LMB using a nickel‐rich layered cathode of LiNi0.76Mn0.14Co0.10O2 (NMC76) and an optimized electrolyte [0.6 m lithium bis(trifluoromethanesulfonyl)imide + 0.4 m lithium bis(oxalato)borate + 0.05 m LiPF6 dissolved in ethylene carbonate and ethyl methyl carbonate (4:6 by weight)] demonstrates excellent stability at a high charge cutoff voltage of 4.5 V. Remarkably, these Li||NMC76 cells can deliver a high discharge capacity of >220 mA h g−1 (846 W h kg−1) and retain more than 80% capacity after 1000 cycles at high charge/discharge current rates of 2C/2C (1C = 200 mA g−1). This excellent electrochemical performance can be attributed to the greatly enhanced structural/interfacial stability of both the Ni‐rich NMC76 cathode material and the Li metal anode using the optimized electrolyte. Excellent rate capability and cycling performance in a high voltage lithium (Li) metal battery (LMB) composed of Ni‐rich layered LiNi0.76Mn0.14Co0.10O2 (NMC76) and Li metal are enabled by the formation of stable electrode/electrolyte interfaces in an optimized dual‐salt electrolyte with additive. The Li||NMC76 cell demonstrates a capacity retention above 80% after 1000 cycles at 400 mA g−1 between 2.7–4.5 V.